2016
DOI: 10.21037/jss.2016.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of far lateral lumbar disc herniation: a safe and simple approach

Abstract: Lumbar discectomy is one of the most commonly performed neurosurgical procedure. Far lateral disc herniations (FLDH) make up a minor portion of the total discectomy workload for spine surgeons. Due to their lower incidence, as well as their different anatomical positioning compared to the more common para-median disc herniation, the surgical procedures involved in releasing the neural compression caused by FLDHs are often challenging and at times frustrating to most spine surgeons, resulting in suboptimal outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 8 publications
0
18
1
Order By: Relevance
“…In addition, inherently difficult anatomic access to the lateral interpedicular compartment may increase risk of causing nerve damage, or damaging the overlying facet joint, which can place the patient at risk of spine instability, resulting in spinal fusion surgery in the future. 1,2 However, despite the notion that far lateral HNP may be associated with a technically more difficult surgical procedure, our study has found that patients presenting with far lateral disc herniations can expect similar outcomes to patients presenting with central/paracentral herniations with no increased risk of reoperation. This information can be used in support of surgical treatment for far lateral HNP, as previous literature has suggested that conservative management may result in relatively high non-operative success rates.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In addition, inherently difficult anatomic access to the lateral interpedicular compartment may increase risk of causing nerve damage, or damaging the overlying facet joint, which can place the patient at risk of spine instability, resulting in spinal fusion surgery in the future. 1,2 However, despite the notion that far lateral HNP may be associated with a technically more difficult surgical procedure, our study has found that patients presenting with far lateral disc herniations can expect similar outcomes to patients presenting with central/paracentral herniations with no increased risk of reoperation. This information can be used in support of surgical treatment for far lateral HNP, as previous literature has suggested that conservative management may result in relatively high non-operative success rates.…”
Section: Discussioncontrasting
confidence: 53%
“…Lumbar discectomy for treatment of lumbar radiculopathy remains one of the most common surgical procedures in the United States. 1,2 The common place nature of this procedure makes it important to understand the outcomes expected after specific subtypes of lumbar disc herniation. While the natural course of paracentral and central disc herniations is well documented, less is known about outcomes following far lateral HNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Far lateral lumbar disc herniation (FLLDH), also called extraforaminal lumbar disc herniation, is a special type of lumbar disc herniations (LDHs) and rstly described by Abdullah in 1974 [1]. It consists of foraminal and extraforaminal LDHs, and accounts for 0.7%~11.7% of all LDHs [2,3]. The pathogenesis of FLLDH is different from that of intraspinal central or paracentral disc herniations.…”
Section: Introductionmentioning
confidence: 99%
“…F ar lateral lumbar disc herniation (FLDH), in which the herniated fragment migrates to the underneath and lateral side of the facet joint, is also known as foraminal, intraforaminal or extreme lateral disc herniation in the literature 1 . FLDH is detected in 0.7-12% of all lumbar disc herniations [1][2][3][4] in which the nerve root compression occurs at the same level of herniated disc, rather than at inferior root as in median and paramedian disc herniations (Figure 1). Because of FLDH locates at the outside of spinal canal, it can be hidden and unrecognisable by routine conventional imagings.…”
mentioning
confidence: 99%